Carbon sequestration in tea soil through burial of pruning and its impact on biomass production and soil characteristics - Mathew, Siby; Kumar, R. Raj; Marichamy, M.; Kumar, P. Mohan (Journal of Plantation Crops, 2012)
Global warming and climate change issues force the scientists to focus their attention on carbon sequestration by the terrestrial vegetation. Tea being a perennial crop, its pruned litters contribute to the organic carbon addition to the soils. In this context, randomized block design experiment was conducted to quantify the addition of organic carbon in tea plantations with respect to burial of pruning. Soils of the experimental plots were sampled regularly and subjected to nutrient analysis and population density of soil micro flora. On recovery, economically important crop shoots harvested at regular interval were recorded. There was a significant variation in the biomass produced over a period of one pruning cycle. Complete removal of pruned litter from the tea field registered lower quantum of biomass; however, it supported favourable compartmentalization in terms of economic yield which reflected upon the productivity index (54.86) at the cost of reduction in carbohydrate reserves in the roots. In other words about 55% of organic carbon was harvested as economic yield in burial of pruning. In terms of carbon sequestration, ~3.0 tons of organic carbon was removed as biomass in pruned year (in control blocks) while as high as 4.8 tons organic carbon/ha sequestrated where the burial of pruned litters was adopted. Organic carbon content of both the surface and bottom soils were significantly higher when the pruned litters were buried in the trenches. Post treatment results confirmed an increase in the populations of total bacteria, fungi, Trichoderma spp., Actinomycetes, Azosprillum spp, Phosphate solubilising bacteria and Pseudomonas spp. Even though burial of pruning is a laborious process, when considering the issues on global warming, this could be adopted in tea plantations as a measure of carbon sequestration, which in turn improved the soil fertility, soil micro flora and the economic yield besides the total biomass production. Data generated on enhanced economic yield and total biomass production are presented and discussed in terms of carbon sequestration and clean development mechanism.